Growth of aligned polypyrrole acicular nanorods and their application as Pt‐free semitransparent counter electrode in dye‐sensitized solar cell. (22nd August 2017) - Jha, Purushottam; Veerender, P.; Koiry, S.P.; Sridevi, C.; Chauhan, A.K.; Muthe, K.P.; Gadkari, S.C.
Abstract : Polypyrrole films on fluorine doped tin oxide (FTO)‐coated glass substrate were prepared in situ by placing FTO/glass substrates where pyrrole was polymerized by methyl orange‐ferric chloride complex. The atomic force microscopy image indicated growth of acicular nanorods of polypyrrole. These films exhibited catalytic activity towards I3 − /I − redox couple and have been investigated for counter electrode application in dye‐sensitized solar cell (DSSC). The fabricated DSSC with N719 dye/TiO2 as photoanode, and PPy/FTO as counter electrode shows 1.7% efficiency.